Silence is Golden: A Source Location Privacy Scheme for Wireless Sensor Networks Based on Silent Nodes. (18th November 2022) - Gu, Chen; Jhumka, Arshad; Maple, Carsten
Abstract : Source location privacy (SLP) is an important property for security-critical wireless sensor network applications such as monitoring and tracking. However, cryptology-based schemes cannot protect the SLP effectively since an adversary can capture the source node regardless of the contents of messages. Most techniques use fake sources or message delay to provide SLP, but at the cost of high energy consumption or high message delivery latency. In this paper, we present a new technique to address SLP by selecting sets of nodes that are to be silent for a short period, forcing an attacker to either be delayed or to trace back to the source along a longer route. As such, we make a number of important contributions: (i) we formalise the silent nodes selection (SiNS) problem, (ii) we prove it to be NP-complete, and (iii) to circumvent the high complexity of SiNS, we propose a novel SLP-aware routing protocol. Results from extensive simulations show that our proposed routing protocol provides a high level of SLP under appropriate parameterization at the expense of only negligible latency and messages overhead.